Unlocking cellular barriers: silica nanoparticles and fullerenol conjugated cell-penetrating agents for enhanced intracellular drug delivery - Ravelo-Nieto, Eduardo; Cifuentes, Javier; Ruiz Puentes, Paola; Rueda-Gensini, Laura; Quezada, Valentina; Ostos, Carlos; Muñoz-Camargo, Carolina; Reyes, Luis H.; Duarte-Ruiz, Alvaro; Cruz, Juan C. (Frontiers in Bioengineering and Biotechnology, 2023)
The limited delivery of cargoes at the cellular level is a significant challenge for therapeutic strategies due to the presence of numerous biological barriers. By immobilizing the Buforin II (BUF-II) peptide and the OmpA protein on magnetite nanoparticles, a new family of cell-penetrating nanobioconjugates was developed in a previous study. We propose in this study to extend this strategy to silica nanoparticles (SNPs) and silanized fullerenol (F) as nanostructured supports for conjugating these potent cell-penetrating agents. The same molecule conjugated to distinct nanomaterials may interact with subcellular compartments differently. On the obtained nanobioconjugates (OmpA-SNPs, BUF-II-PEG12-SNPs, OmpA-F, and BUF-II-PEG12-F), physicochemical characterization was performed to evaluate their properties and confirm the conjugation of these translocating agents on the nanomaterials. The biocompatibility, toxicity, and internalization capacity of nanobioconjugates in Vero cells and THP-1 cells were evaluated in vitro. Nanobioconjugates had a high internalization capacity in these cells without affecting their viability, according to the findings. In addition, the nanobioconjugates exhibited negligible hemolytic activity and a low tendency to induce platelet aggregation. In addition, the nanobioconjugates exhibited distinct intracellular trafficking and endosomal escape behavior in these cell lines, indicating their potential for addressing the challenges of cytoplasmic drug delivery and the development of therapeutics for the treatment of lysosomal storage diseases. This study presents an innovative strategy for conjugating cell-penetrating agents using silica nanoparticles and silanized fullerenol as nanostructured supports, which has the potential to enhance the efficacy of cellular drug delivery.